GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 48 species occurrences available in GBIF matching the query: TaxonKey: Cephalocereus apicicephalium E.Y.Dawson DatasetKey: Cactáceas Columnares de México (IE-MORELIA, UNAM). The dataset includes 48 records from 1 constituent datasets: 48 records from Cactáceas Columnares de México (IE-MORELIA, UNAM).
Keywords: GBIF; biodiversity; species occurrences